Internal Thoracic Artery Patency Before and After Insertion of Specially Designed Pectus Bar - (:unkn) unknown (My University, 2016)
Amaç: Kunduracı göğsü (pektus ekskavatum-PE) minimal invaziv yöntemle onarılmış (MIRPEx) hastalarda internal torasik arterler (İTA'lar) içinden geçen kan akımı bloke olabilir. Bu çalışmanın amacı İTA'ları koruma amacıyla özellikle tasarlanmış pektus barları kullanılarak MIRPEx olmuş hastalarda İTA'ların patensini araştırmaktı.Gereç ve Yöntem: Bu çalışmaya, PE düzeltmesi yapılacak olan 16 yaş üstü 22 hasta dahil edildi. Daha önceden PE nedeniyle ameliyat edilen hastalar çalışmaya alınmadı. Bilgisayarlı tomografi-anjiyografi (BTA) tüm hastalara İTA akımını değerlendirmek için ameliyat öncesi yapıldı. Tüm hastalar özel tasarım pektus barı ile ameliyat edildi. Ameliyat sonrası 10. günde toraksın kontrol BTA'sı çekildi. Ameliyat öncesi ve sonrası BTA'lar İTA akımını değerlendirmek amacıyla karşılaştırıldı.Bulgular: Çalışma grubunda 19 erkek 3 kadın hastanın yaş ortalamaları 18.81±2.48 (dağılım, 16-23 yıl) idi. On sekiz hastada kan akımı etkilenmemişti (%88.8) ve sadece dört hastada tek taraflı İTA tıkanması mevcuttu.Sonuç: Sonuçlar, benzersiz bir şekilde tasarlanmış barla MIRPEx sonrasında, 5 hastanın sadece 1'inde tek taraflı İTA tıkanması olduğunu gösterdi

Background: Blood flow in internal thoracic arteries (ITAs) may become blocked in patients who have had minimally invasive repair of pectus excavatum (MIRPEx). Aim of this study was to investigate patency of ITAs in patients who underwent MIRPEx with pectus bars that were specially designed to protect ITAs.Methods: Total of 22 patients over the age of 16 years who were to undergo correction of pectus excavatum (PEx) were included in this study. Patients with previous surgical intervention for PEx were excluded. Computed tomography-angiography (CTA) of the thorax was performed preoperatively on all patients to evaluate ITA blood flow. MIRPEx procedure included use of specially designed bars in all cases. On postoperative 10th day, follow-up CTA of the thorax was performed. Pre- and postoperative CTAs were compared to determine any effect of bars on ITAs.Results: Study group comprised 19 male patients and 3 female patients; mean age was 18.81±2.48 years (range: 16–23 years). Blood flow was not affected in 18 patients (88.8%) and was unilaterally blocked in 4 patients (18.2%) after the operation.Conclusion: Results demonstrate that only 1 in 5 patients had unilateral ITA occlusion following MIRPEx with uniquely designed bar
Özel Tasarlanmış Pektus Barı Yerleşimi Öncesi ve Sonrasında İnternal Torasik Arter Akımının Değerlendirilmesi
Keywords: Genel ve Dahili Tıp